Factors Affecting Child Marriage in West Nusa Tenggara - Rofita, Desi; Makmun, Indriyani; Amilia, Rizkia; Lestari, Cahaya Indah; Sofiatun, Sofiatun (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2023)
Background: Child marriage is a significant problem millions of girls face every year. During the period of 2015 – 2018, the increase and decrease in prevalence at the provincial level varied in magnitude. There are 11 provinces that experience marriage for the first time in less than 18 years. One of them is the Province of Nusa Tenggara by 15.48%. The purpose of this research is to observe the factors affecting the incidence of child marriage.Method: This is a quantitative research using secondary data from the Survey of Program Accountability and Performance (SKAP) in West Nusa Tenggara Province, Indonesia as many as 1,292 women of childbearing age. Independent variables included age, education level, occupation, and area of residence; while dependent variable referred to child marriage.Results: There was a significant relationship between age and 95% CI = 1.151-1.754 (p = 0.00), education level and 95% CI = 1.997-3.111, (p = 0.00), employment status and 95% CI = 0.564- 0.895, (p = 0.00), information exposure and 95% CI = 1.178-2.672, (p = 0.00), on the incidence of child marriage. Respondents not attending school had a 2.4 times risk of child marriage, while information exposure has a chance of child marriage, as indicated by a prevalence ratio of 1.7. The area of residence did not have a significant relationship with child marriage with 95% CI = 0.821-1.305, (p = 0.76). The results showed that there was a significant relationship between age, education level, employment status, and information exposure to child marriage. The area of residence did not have a significant relationship with child marriage. Therefore, it is necessary to increase the knowledge of women of childbearing age by providing education such as counseling about the impacts of child marriage.